Pengaruh Kualitas Pelayanan, Pemahaman Peraturan dan Sanksi Perpajakan Pada Kepatuhan WPOP - Widian, I Made Yoga; Jati, I Ketut (E-Jurnal Akuntansi, 2019)
One way to increase government revenue from the tax sector is by increasing taxpayer compliance itself. The purpose of this study was to determine the effect of service quality, understanding of regulations and taxation sanctions on individual taxpayer compliance registered at North Badung KPP Pratama. The study was conducted at the KPP Badung Utara in 2018. The sample selection was 100 taxpayers using the Slovin formula. Data collection was carried out by distributing questionnaires to WPOP registered in North Badung KPP Pratama and the analysis techniques using multiple linear regression analysis. Based on the results of the analysis, it is known that service quality, understanding of regulations and taxation sanctions have a positive effect on individual taxpayer compliance registered in North Badung KPP Pratama, with the value of calculating each variable greater than the label, and having a significance value greater than 0.05. Keywords : Quality Of Service;  Understanding Of Tax Regulations; Tax Sanctions; Individual Taxpayer Compliance.